Penggunaan Eceng Gondok dalam Pengolahan Air Bekas Galian Tambang Batubara untuk Perumahan di Kota Samarinda - M. Dwi Triosusanto; Shalaho Dina Devy; Revia Oktaviani; Windhu Nugroho; Lucia Litha Respati (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The implementation of coal mining activities with an open pit system at the end of its activities will leave behind the remains of former mining holes. Control of acid mine water is something that needs to be done during mining activities until the end of the mining process because acid mine water can cause a decrease in the quality of surface water and groundwater and have an impact on the survival of humans and biota that live on land and water. The initial characteristics of water using the floating treatment method of wetland, the pH, TSS, Fe, and Mn values ​​of ex-mining lake water do not meet the quality standards of the Government Regulation of the Republic of Indonesia Number 22 of 2021. The ability of water hyacinth plants to increase pH for 25 days is quite good with an initial pH value of 4.13 to 7.34. For 25 days, the TSS parameter of water hyacinth plants is also good at reducing TSS levels with an initial value of 6 mg/L to 3 mg/L, the Fe parameter of water hyacinth plants is also good at reducing iron levels with an initial value of 1.06 mg/L to 0.34 mg/L, while the Mn parameter of water hyacinth plants is quite good at reducing manganese levels with an initial value of 1.13 mg/L to 0.32 mg/L.